The main component of the aphid alarm pheromone (E)-β-farnesene affects the growth and development of Spodoptera exigua by mediating juvenile hormone-related genes - Sun, Yang; Li, Yan; Zhang, Wen; Jiang, Bin; Tao, Si-Min; Dai, Han-Yang; Xu, Xin-Tong; Sun, Yue-Xin; Yang, Lei; Zhang, Yong-Jun (Frontiers in Plant Science, 2022)
The (E)-β-farnesene (EβF) is one of the most important secondary metabolites in some plants and provides indirect defense against aphids. However, the direct effect of EβF against pests is still unclear. In this study, various concentrations of EβF (0.16 g/kg, 0.8 g/kg, and 4 g/kg) were provided in an artificial diet to determine the direct effects of EβF on Spodoptera exigua. The results showed that an artificial diet containing 4 g/kg of EβF reduced the final survival of the S. exigua larvae and per female fecundity of adults significantly when compared with CK and SC controls (p < 0.05), then ultimately it also significantly affected the intrinsic rate of increase (p < 0.05). Furthermore, the results of EβF bioassay in an artificial diet also indicated that the proliferation of the S. exigua population was inhibited by the ingestion of EβF in a dose-dependent manner. Combined differential RNA-seq data and RT-qPCR analysis, it was found that four key genes involved in juvenile hormone degradation significantly upregulated in S. exigua larvae treated by EβF at dose of 0.8 g/kg and 4 g/kg when compared with two controls (p < 0.05). This indicated that EβF could disturb the normal function of juvenile hormone and reduce the survival rate of S. exigua larvae. Additionally, two key genes that regulate per fecundity of S. exigua females, including SeVg and SeVgR, were significantly downregulated in adult females (p < 0.05) when they were treated with 0.8 g/kg and 4 g/kg of EβF at the larval stage, relative to the expression of these genes after treatment with controls. These findings suggested that EβF first disturbed the normal function of juvenile hormone by upregulating key degradation genes, and then inhibited the expression of SeVg/SeVgR genes and proteins, thus reducing the population size of S. exigua by increasing larval mortality and inhibiting per female fecundity.